2023
DOI: 10.1071/rd22210
|View full text |Cite
|
Sign up to set email alerts
|

Secreted metabolome of porcine blastocysts encapsulated within

Abstract: Context. The exact mechanisms regulating the initiation of porcine conceptus elongation are not known due to the complexity of the uterine environment. Aims. To identify contributing factors for initiation of conceptus elongation in vitro, this study evaluated differential metabolite abundance within media following culture of blastocysts within unmodified alginate (ALG) or Arg-Gly-Asp (RGD)-modified alginate hydrogel culture systems. Methods. Blastocysts were harvested from pregnant gilts, encapsulated within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Such data could be combined with other models of tissue elongation in order to highlight common themes, including patterning, spatiotemporal cell fate, or physical forces that enable proper morphogenesis ( Horne-Badovinac, 2014 ; Weng et al, 2022 ; Adler et al, 2023 ). Taken together, our results provide useful information for the future analyses of the factors that coordinate the conserved morphogenetic processes at work during bovine conceptus development, processes that one may evaluate in the coming years through novel cell culture modes ( Walsh et al, 2023 ), cocultures ( Wei et al, 2023 ), or in silico predictive models ( Butt et al, 2023 ).…”
Section: Discussionmentioning
confidence: 82%
“…Such data could be combined with other models of tissue elongation in order to highlight common themes, including patterning, spatiotemporal cell fate, or physical forces that enable proper morphogenesis ( Horne-Badovinac, 2014 ; Weng et al, 2022 ; Adler et al, 2023 ). Taken together, our results provide useful information for the future analyses of the factors that coordinate the conserved morphogenetic processes at work during bovine conceptus development, processes that one may evaluate in the coming years through novel cell culture modes ( Walsh et al, 2023 ), cocultures ( Wei et al, 2023 ), or in silico predictive models ( Butt et al, 2023 ).…”
Section: Discussionmentioning
confidence: 82%
“…The same research group conjugated alginate hydrogels with Arg-Gly-Asp and it increased the embryo survival and induced morphological changes, when compared to the normal alginate hydrogel ( Laughlin et al, 2017 ). This model was recently used to study metabolome changes during the elongation process, which identified changes in secreted metabolites that may be correlated with the elongation mechanism ( Walsh et al, 2023 ).…”
Section: Use Of 3d Cultures For Gametes and Embryo Manipulationmentioning
confidence: 99%
“…In (C) bovine embryos were cultured in groups of 5 encapsulated inside an alginate bead or in conventional culture(Yániz et al, 2002). In (D) porcine blastocysts were cultured in a two-layered alginate bead to support its development after hatching(Sargus-Patino et al, 2014;Laughlin et al, 2017;Walsh et al, 2023). In (E) bovine blastocysts in the hatching stage were cultured in an alginate bead or alginate overlay(Zhao et al, 2015).Figure made with Biorender.…”
mentioning
confidence: 99%